Full-Color Quantum Dot Light-Emitting Diodes Based on Microcavities - Guanding Mei; Weigao Wang; Dan Wu; Philip Anthony Surman; Kai Wang; Wallace C. H. Choy; Xiaochuan Yang; Wenwei Xu; Xiao Wei Sun (IEEE Photonics Journal, 2022)
Full-color display is a primary challenge for the commercialization of quantum dots (QDs). In this study, we utilize the spectral narrowing phenomenon of microcavities to fabricate the red, green and blue quantum dot light-emitting diodes (QLEDs) with a single QD layer. This work theoretically analyses the role of microcavities in adjusting the emitting color of QLEDs. By enhanced microcavity and properly chosen spacer thickness, the spectral selectivity shifts, realizing the full-color-tunability of QLEDs. The tunable experimental spectra of microcavity QLEDs are observed, in excellent agreement with our theoretical design. Benefiting from the spectral narrowing of microcavity and the narrow spectra of QDs, a high color purity with full width at half maximum (FWHM) of 18 to 25 nm is realized, leading to a color gamut ratio of 104.8% compared to National Television System Committee (NTSC) standard. The light extraction is also enhanced by constructive interference and the Purcell effect in the microcavity. Moreover, in the fabrication of red, green, and blue pixels, patterning the transparent cathode has better feasibility and lower damage relative to patterning the light-emitting layer.